Beach Ecotourism on Beras Basah Island, Bontang City, East Kalimantan - Mona Lisa Panjaitan; Muhammad Yasser; Widya Kusumaningrum; Omega Raya Simarangkir (Berkala Perikanan Terubuk, 2021)
Beras Basah Island is an object pride tourism in Bontang City. The island is located in the middle of thesea and surrounded by beautiful beaches by width about one hectare. In addition from being a beautifulisland with white sand, this island is also a water area surrounded by a lot of biodiversity such as a coralreefs, seagrass beds, and various types of fish. This study aimed to find out the Tourism Suitability Indexand area supporting effort for coastal tourism on Beras Basah Island, Bontang City, East Kalimantan. Thisresearch was conducted in March 2021. The research location was in Pulau Beras Basah city. Analysis ofthe data used Tourism Suitability Indeks based on the multiplication of weights and skors obtained fromeach parameter of Depth, Brightness, coast type, coast Width, Coastal Slope, Water Base Material,Current Speed, tracking of Hazardous Biota, Land Closure, Water Availability, and using Area SupportingEffort analysis Based on the size of the seashore area. The condition of the beach tourism suitability indexfor the four stations on Beras Basah Island is the north station 2,3, 2,5 east, 2,6 south and west station 2,5the category is very suitable even though the visual conditions in the field actually look general and aresuitable for ecotourims and tourims. The total area carrying capacity calculation results are estimated tohave a maximum capacity of 202 people/day in 5 hours/person.